Recent advances in understanding hematopoiesis in Fanconi Anemia [version 1; referees: 4 approved] - Grover Bagby (F1000Research, 2018)
Fanconi anemia is an inherited disease characterized by genomic instability, hypersensitivity to DNA cross-linking agents, bone marrow failure, short stature, skeletal abnormalities, and a high relative risk of myeloid leukemia and epithelial malignancies. The 21 Fanconi anemia genes encode proteins involved in multiple nuclear biochemical pathways that effect DNA interstrand crosslink repair. In the past, bone marrow failure was attributed solely to the failure of stem cells to repair DNA. Recently, non-canonical functions of many of the Fanconi anemia proteins have been described, including modulating responses to oxidative stress, viral infection, and inflammation as well as facilitating mitophagic responses and enhancing signals that promote stem cell function and survival. Some of these functions take place in non-nuclear sites and do not depend on the DNA damage response functions of the proteins. Dysfunctions of the canonical and non-canonical pathways that drive stem cell exhaustion and neoplastic clonal selection are reviewed, and the potential therapeutic importance of fully investigating the scope and interdependences of the canonical and non-canonical pathways is emphasized.